What percentages of patients are suitable for prehospital thrombolysis?. Issue 6 (19th May 2006) - Castle, N; Owen, R; Vincent, R; Ineson, N
Abstract : Objective: To apply the Joint Royal College Ambulance Liaison Committee (JRCALC) checklist to patients who were deemed eligible for thrombolytic therapy on arrival in an Accident & Emergency Department (A&E) to determine the proportion suitable for prehospital thrombolysis. Design: Retrospective descriptive analysis. Methods: The clinical notes of all patients thrombolysed in an A&E department in a year were reviewed against the JRCALC guidelines for prehospital thrombolysis. Results: 14.2% of patients eligible for thrombolysis in a district general hospital were deemed suitable for prehospital thrombolysis according to the JRCALC criteria. The most common exclusion criteria were hyper/hypotension (50%), onset of symptoms (pain) >6 h previously (41.7%), or age >75 years (37%). Two or more contraindications to prehospital thrombolysis were present in 63.9% of patients. Conclusion: The JRCALC guidelines are an effective tool for identifying patients with potential contraindications to thrombolysis.